The behaviour of metal(oid)s contaminants in woody biomass during advanced thermal conversion processes. - Al-Badri, Shurooq Badri (Cranfield University, 2019)
A remarkable proportion (about 64%) of renewable biomass energy is produced from woody biomass (wood and its wastes). However, waste wood (WW) often exhibits a high level of chemical contaminants, likely due to the presence of metal(loid) elements in preservatives, paintings, coatings, and other related activities. By thermally treating WW, the metal(loid)s will end up in the bottom ash and/or be emitted into the atmosphere, causing severe environmental concerns and technical damages (e.g. slagging and corrosion). Thus, it is necessary to understand the behaviour of metal(loid)s during the woody biomass thermal conversion process, specifically gasification and pyrolysis. While a great deal of knowledge is available on this matter, there is still uncertainty surrounding the identification and characterisation of metal(loid) elements in relation to woody biomass utilisation, as well as the influences of reaction atmosphere composition in terms of interactions and interferences. In addition to that, knowledge is needed on partitioning profiles of the key metal(loid) elements during the gasification and pyrolysis of WW in order to evaluate the emission potential of these elements. This thesis firstly provides a highly informative dataset that contains comprehensive details about the characterisation and elemental composition of key metal(loid) elements (As, B, Co, Cr, Cu, Fe, Ni, Pb, Mn, Hg and Ti) that are regularly present in woody biomass. Moreover, chemical equilibrium calculations were performed to predict elemental phase transformation and speciation formation under given gasification and pyrolysis operation conditions. Among the results, it was found that Ni-As interactions form the dominant species As₂Ni₅ and As₈Ni₁₁, which increase the solid-gaseous phase transformation of As. In addition, the Ca-Cr interaction forms C₃Cr₇; meanwhile, the absence of Ca creates instability in the Cr phase transformation due to the generation of the species Cr₂Na₂O₄. Subsequently, a set of experiments were conducted using a TGA analyser with different heating rates to understand the thermal behaviour of woody biomass and define the operational conditions of the pyrolysis process. Tube furnace experiments were also conducted to investigate the distributions of Al, As, Ca, Cd, Co, Cr, Cu, Fe, Hg, K, Na, Mn, Mo, Ni, Pb, Si, Ti, V, and, Zn during the operation of pyrolysis. Experimental results indicated that Cd and Hg are exceedingly volatile elements, whereas Al, Co, Cr, Cu Fe, Mo, Ni, Si, Ti, and V are non-volatile elements. The elements As, Mn, Pb, and Zn exhibited differences in partitioning across all experiments. Importantly, this study provides unique insight into the behaviour of As in terms of As-Ni interaction. That is, the presence of Ni should be regarded in combination with its associated concentration profile. Finally, the experimental data and the calculation results are complementary rather than competitive. Overall, the experimental results are within acceptable validation limits.
Keywords: Wood waste; advanced thermal conversion; thermodynamic equilibrium modelling; interactions; interferences; gasification; pyrolysis